Isolated Hemolysis Profile of Streptococcus Sp. Isolation Result from Swine’s Tonsil In Slaughter House at Punggul and Bongkasa Village - Naomi, Carene; Suardana, I Wayan; Suarsana, I Nyoman (Journal of Veterinary and Animal Sciences; Vol 2 No 2 (2019), 2019)
Streptococcus is a Gram-positive coccus from the family Streptococcaceae that can be found normally in some healthy animal but can cause a disease as well. The purpose of this research is to know the hemolysis profile from pig’s tonsil swab isolated from the traditional pig slaughterhouse at Punggul Village and Bongkasa Village that can be divided into three hemolytic profile; alpha-hemolytic, beta hemolytic, and gamma hemolytic, to know the pathogenicity. This research is divided into several steps, such as; isolating the swab, Gram test, catalase test, oxidase test, and hemolysis test on Sheep Blood Agar. Streptococcus is a Gram-positive coccus, tested Gram positive, catalase negative and oxidase positive. This research concludes the amount of positive Streptococcus sp sample based on hemolysis profile is 6 of 24 samples, whereas 3 of 24 samples (12,5%) has ? hemolysis pattern, 3 of 24 samples (12,5%) has ? hemolysis pattern and none showed the ? pattern. The conclusion from the table; showed positive sample of Streptococcus sp is divided 50:50 for the ? and ? hemolysis, and no sample showed the ? pattern. At most cases, the ? and ? hemolysis Streptococcus is a pathogen bacterium. This data might be useful for references to see the transmission of Streptococcus sp in swine at Abiansemal area in Badung, Bali